Hasselblad Foundation, Sweden Commissioned Work - Stylianou-Lambert, Theopisti (My University, 2026)
This is a commissioning work award. Two international artists/groups of artists were selected in 2024 to create new works for the exhibition "Bugs and Metamorfosis" which will take place at the Hasselblad Foundation. The opening is on February 7th 2025
Keywords: Arts and entertainment